2014
DOI: 10.1111/imb.12155
|View full text |Cite
|
Sign up to set email alerts
|

Three Halloween genes from the Varroa mite,Varroa destructor(Anderson & Trueman) and their expression during reproduction

Abstract: The ecdysteroid biosynthetic pathway involves sequential enzymatic hydroxylations by a group of enzymes collectively known as Halloween gene proteins. Complete sequences for three Halloween genes, spook (Vdspo), disembodied (Vddib) and shade (Vdshd), were identified in varroa mites and sequenced. Phylogenetic analyses of predicted amino acid sequences for Halloween orthologues showed that the acarine orthologues were distantly associated with insect and crustacean clades indicating that acarine genes had more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
48
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(50 citation statements)
references
References 58 publications
2
48
0
Order By: Relevance
“…These genes included two vitellogenins ( Vd Vg1, Vd Vg2) [33], a large lipid transfer protein ( Vd LLTP) [34], foraging ( Vd For) and malvolio ( Vd Mvl) [60], spook ( Vd spo), disembodied ( Vd dib), shade ( Vd shd) [59] and a co-transcription factor subolesin ( Vd sub) (Cabrera and Shirk, unpublished data). Comparison of the transcript levels for each of the nine selected genes between untreated control phoretic mites and the phoretic mites that survived the feeding protocol showed that that there were no significant differences after completing the feeding protocol (VdLLTP: t = -1.13, p = 0.3228, n = 3; VdVg1: t = 1.97, p = 0.1195, n = 3; VdVg2: t = 1.12, p = 0.3260, n = 3; VdFor: t = -1.20, p = 0.2964, n = 3; VdMvl: t = -1.87, p = 0.1341, n = 3; Vdspo: t = -1.35, p = 0.2475, n = 3; Vddib: t = -1.70, p = 0.1640, n = 3; Vdshd: t = -1.12, p = 0.3274, n = 3; Vdshd: t = -1.12, p = 0.3247; Vdsub: t = -0.84, p = 0.4468, n = 3); Fig 4).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…These genes included two vitellogenins ( Vd Vg1, Vd Vg2) [33], a large lipid transfer protein ( Vd LLTP) [34], foraging ( Vd For) and malvolio ( Vd Mvl) [60], spook ( Vd spo), disembodied ( Vd dib), shade ( Vd shd) [59] and a co-transcription factor subolesin ( Vd sub) (Cabrera and Shirk, unpublished data). Comparison of the transcript levels for each of the nine selected genes between untreated control phoretic mites and the phoretic mites that survived the feeding protocol showed that that there were no significant differences after completing the feeding protocol (VdLLTP: t = -1.13, p = 0.3228, n = 3; VdVg1: t = 1.97, p = 0.1195, n = 3; VdVg2: t = 1.12, p = 0.3260, n = 3; VdFor: t = -1.20, p = 0.2964, n = 3; VdMvl: t = -1.87, p = 0.1341, n = 3; Vdspo: t = -1.35, p = 0.2475, n = 3; Vddib: t = -1.70, p = 0.1640, n = 3; Vdshd: t = -1.12, p = 0.3274, n = 3; Vdshd: t = -1.12, p = 0.3247; Vdsub: t = -0.84, p = 0.4468, n = 3); Fig 4).…”
Section: Resultsmentioning
confidence: 99%
“…All transcript levels were normalized to the geometric mean of actin and GAPDH transcript levels and presented as fold differences as reported previously [59]. Black bars are phoretic mites and gray bars represent mites completing feeding protocol.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations